2022
DOI: 10.3389/fimmu.2022.905423
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NLRP3 Inflammasome Activation Pathway of Hepatic Macrophages in Liver Ischemia–Reperfusion Injury

Abstract: Ischemia-reperfusion injury (IRI) is considered an inherent component involved in liver transplantation, which induce early organ dysfunction and failure. And the accumulating evidences indicate that the activation of host innate immune system, especially hepatic macrophages, play a pivotal role in the progression of LIRI. Inflammasomes is a kind of intracellular multimolecular complexes that actively participate in the innate immune responses and proinflammatory signaling pathways. Among them, NLRP3 inflammas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“… 31 NLPR3 is highly expressed in hepatic macrophages, and NLRP3 inflammasome activation plays an important role in promoting inflammatory liver IR injury. 32 We have previously found that aging aggravates liver IR injury by promoting macrophage NLRP3 activation. 8 19 A recent study also found that NLRP3 mediates the inflammatory response and pyroptosis in macrophages during fatty liver IR injury.…”
Section: Discussionmentioning
confidence: 96%
“… 31 NLPR3 is highly expressed in hepatic macrophages, and NLRP3 inflammasome activation plays an important role in promoting inflammatory liver IR injury. 32 We have previously found that aging aggravates liver IR injury by promoting macrophage NLRP3 activation. 8 19 A recent study also found that NLRP3 mediates the inflammatory response and pyroptosis in macrophages during fatty liver IR injury.…”
Section: Discussionmentioning
confidence: 96%
“…The sterile inflammatory response of HIRI was diven by innate immunity initiated by recognizing pattern-recognition receptors (PRRs), including NLRP3 ( 2 , 24 , 25 ). NLRP3 has been identified as a major contributor to liver injury and amplification of liver inflammation, making it a promising therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages have been recognized as the main cells responsible for NLRP3 activation via ROS production during LIRI [70,86]. In fact, the knockdown of NLRP3 in mice leads to a reduction of serum alanine aminotransferase levels and a decreased production of pro-inflammatory cytokines such as IL-1β, IL-18, IL-6, and TNFα, leading to liver protection from ischemia-reperfusion damage [87].…”
Section: Type Of Cld Effect Sex and Species Referencesmentioning
confidence: 99%